The Effect of Implementing Green Logistics and Reducing Carbon Emissions on The Operational Efficiency Of Logistics Companies - Najla Khairunnisa Setiyanto; Arini Ulfa Mawaddah; Erni Pratiwi Perwitasari; Amrulloh Ibnu Kholdun (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Increased emissions of greenhouse gases such as carbon dioxide have made global warming and climate change a major problem worldwide. According to World Air Quality Report data, the Special Capital Region (DKI) Jakarta ranks seventh as the largest contributor to emissions in 2023. This study aims to determine the implementation of the effect of implementing green logistics and reducing carbon emissions on the operational efficiency of logistics companies as an effort to support the Indonesian Government committed to the International Sustainable Development Goals (SDGs) to reduce greenhouse gas emissions in Indonesia, especially in the DKI Jakarta area. The research method to be used is a quantitative method with a survey approach and data collected through questionnaires distributed to 35 logistics companies in DKI Jakarta. SEM-PLS (Structural Equation Modeling Partial Least Squares) analysis technique is used for data processing. The results showed that the application of green logistics on the operational efficiency of logistics companies has a positive effect, the implementation of green logistics on reducing carbon emissions has a positive effect, reducing carbon emissions on the operational efficiency of logistics companies has a positive effect, and the application of green logistics on the operational efficiency of logistics companies trough reducing carbon emissions has a positive effect, and the application of green logistics on the operational efficiency of logistics companies trough carbon emission reduction has a positive effect.